Teaching Reform of Literature Retrieval Course under the Accreditation of Engineering Education: The Case of Biological Science Major of Linyi University - Duan, Jiayu (Pacific International Journal, 2024)
The professional certification of engineering education has put forward new requirements for talent training in the new period, and the literature retrieval course can not only cultivate the information quality of students, but also provide strong support for the talent training requirements put forward by the engineering certification as a course with strong practicability. Here we analyze the problems in the process of teaching the literature search course for the bioengineering majors of Linyi University and put forward the corresponding solutions to provide a little experience and suggestions for the reform of other courses in the future.